(untitled) (Research, Society and Development, 2022)
Objective: to identify, through the literature, studies that address self-medication and its relationship with COVID-19. Method: this is an integrative literature review, in which the construction of the study was based on the question “How and which factors influenced the practice of self-medication by the population in the face of the COVID-19 pandemic?”. The bibliographic survey was carried out between June and August 2021, using the PubMed, Cochrane, Scielo and Lilacs databases using the descriptors in Portuguese and English: self-medication / self-medication; Covid-19; pandemics / pandemic. There was no restriction regarding the publication date of the studies. Inclusion criteria: studies that portrayed the practice of self-medication in the face of the COVID-19 pandemic; published in journals, in Portuguese, English and Spanish, with abstract and full text available for reading. Results: the search resulted in twenty-three articles, thirteen in Pubmed, four in Cochrane, two in Lilacs and four in Scielo. The final sample of this review consisted of four articles. Final Considerations: during a pandemic, social isolation, changes in lifestyle, fear of getting sick and dying, scientific denialism and misinformation become responsible for inducing the use of certain drugs based on incipient research and without robust evidence data. scientific evidence of clinical benefit and safety.